Wear and Indentation Resistance of Polyethylene Nanocomposites at High Temperatures - Alghamdi, A. S. (Engineering, Technology & Applied Science Research, 2022)
The presence of nanofillers in the polyethylene matrix can play an important role in changing their behavior during mechanical testing. Moreover, high ambient temperature can seriously affect the properties of polyethylene and cause softening, which leads to a decrease in stiffness, strength, hardness, and wear resistance. In the current work, carbon nanotubes (CNTs) and nanoclays with 0.5wt.% are embedded into polyethylene blend matrix to enhance its mechanical properties, mainly wear and indentation resistance at different ambient temperatures. The results show that the processing method used resulted in homogenous distribution and good dispersion of nanofillers. The addition of 0.5 wt.% CNT or nanoclays increased the indentation and wear resistance at both room and high temperatures. At high temperatures, the presence of nanofillers caused an increase in wear resistance by 32.2% at maximum depth.